Handbook of Food Toxicology - Deshpande, S S (Marcel Dekker, 2002)
From health and economic consequences to exposure assessment and detoxification, this title covers the formation, characteristics, and control of various toxins that occur in the production, storage, and preparation of food. It discusses toxin sources, mechanisms, routes of exposure and absorption, and their chemical and biochemical components.